2019
DOI: 10.1038/s41388-019-0895-2
|View full text |Cite
|
Sign up to set email alerts
|

Rare, functional, somatic variants in gene families linked to cancer genes: GPCR signaling as a paradigm

Abstract: Oncodriver genes are usually identified when mutations recur in multiple tumours. Different drivers often converge in the activation or repression of key cancer-relevant pathways. However, as many pathways contain multiple members of the same gene family, individual mutations might be overlooked, as each family member would necessarily have a lower mutation frequency and thus not identified as significant in any one-gene-at-a-time analysis. Here, we looked for mutated, functional sequence positions in gene fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 75 publications
4
26
0
Order By: Relevance
“…These include mutations localized to the DRY motif, which mediates the inactive conformation of class A GPCRs, with particular emphasis on recurrent mutations in DRY arginine, in addition to the nPxxY motif, both of which are critical regulators of GPCR activation. Mutations in these positions show statistically significant mutual exclusivity between motifs, as well as with activating hotspot mutations in the Gα subunit further supporting the functional significance of these structure‐based predictions [47]. DRY arginine mutations are also mutually exclusive with many common mutant oncogenes that are downstream of GPCR‐mediated signalling cascades, including AKT E17K, PIK3CA E545K, and JAK2 V617F [47].…”
Section: Gpcrs In Cancer Initiation: Proliferative Signalling Evasiomentioning
confidence: 79%
See 2 more Smart Citations
“…These include mutations localized to the DRY motif, which mediates the inactive conformation of class A GPCRs, with particular emphasis on recurrent mutations in DRY arginine, in addition to the nPxxY motif, both of which are critical regulators of GPCR activation. Mutations in these positions show statistically significant mutual exclusivity between motifs, as well as with activating hotspot mutations in the Gα subunit further supporting the functional significance of these structure‐based predictions [47]. DRY arginine mutations are also mutually exclusive with many common mutant oncogenes that are downstream of GPCR‐mediated signalling cascades, including AKT E17K, PIK3CA E545K, and JAK2 V617F [47].…”
Section: Gpcrs In Cancer Initiation: Proliferative Signalling Evasiomentioning
confidence: 79%
“…Strikingly, our recent study found that there is widespread activation of the Gαs pathway across a large proportion of cancer types in TCGA with a remarkable enrichment in cancers of the gastrointestinal tract 47 . Consistent with this, the Gαs subfamily is mutated in 5.24% of colorectal, 5.03% of pancreatic and 5.96% of stomach adenocarcinomas ( Table 1, Table S5).…”
Section: Accepted Articlementioning
confidence: 80%
See 1 more Smart Citation
“…A complicating factor is that most GPCRs do not harbor hotspot mutations, meaning that mutations in each GPCR do not occur with high frequency in a single or limited numbers of codons, and in addition, each tumor exhibits a different repertoire of mutated GPCRs. To address this daunting question, we have recently developed new bioinformatics approaches analyzing GPCR mutations in the context of multiple sequence alignments (MSA) defining the conserved seven-transmembrane (7TM) domain, as well as considering 3D structures and interaction partners (241). We have used this approach to model the most significantly mutated GPCRs (Table S2A).…”
Section: Mutated Oncogpcromementioning
confidence: 99%
“…Although the functional impact of these alterations may need to be investigated for each GPCR, our recent computational analysis of cancer genomes indicates that most G␣ i -linked GPCRs exhibit DRY mutations that are inhibitory in nature (inhibit function), which typically occur mutually exclusively with GNAS9-activating mutations (241). This suggests the exciting possibility that mutations in G␣ i -GPCRs may mimic GNAS mutants leading to higher cAMP activity to drive tumorigenesis (241).…”
Section: Mutated Oncogpcromementioning
confidence: 99%